Hubungan antara Orientasi Religius dan Kecurangan Akademis pada Mahasiswa - Wenti Indrianita; Sri Fatmawati Mashoedi; Eko Aditiya Meinarno (Jurnal Ilmiah Psikologi MIND SET, 2011)
This research was focusing on the relationship between religious orientation and academic cheat among college students. This research was held since many cheating phenomena were increasing in several education levels related with religious orientation. Paloutzian said that religious orientation related with the person's angle on how the person positioned his/her religion in his/her life that determined his/her pattern of relation form with the religion. Religious orientation is divided into two dimensions, internal and external. The issue in this research is whether there is a significant relation or not between the religious orientation and academic cheats. Furthermore, this research had a purpose to know the relations between the religious orientation and academic cheats with the college students. This research found Pearson correlation coefficient between religious orientation and academic cheats was -0.209 and significant 0.005 in the internal religious orientation dimension. There was 0.207 and significant 0.006 in the external religious orientation dimension. Those results have supported the hypothesis of this research. Because of that, the higher internal religious orientation scored, the lower academic cheat conducted. On the other hand, the lower internal religious orientation scored the higher possibility for the college students to get involved in the academic cheats.